2020
DOI: 10.1088/1757-899x/796/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

Warehouse management model using FEFO, 5s, and chaotic storage to improve product loading times in small- and medium-sized non-metallic mining companies

Abstract: This article addresses one of the main problems faced by small- and medium-sized business in the non-metallic mining sector in Peru. These companies own warehouses and face the major problem of failing to deliver orders correctly and in a timely manner. This problem usually occurs when the business grows from a small- to medium-sized company in a short span of time; this situation leads to new processes within warehouses that are mostly not standardized. Besides, facilities are no longer optimal in space and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
3
0
3
Order By: Relevance
“…Metode FEFO atau First Expired First Out adalah metode manajemen persediaan yang didasarkan pada prinsip bahwa barang dengan jangka waktu kadaluarsa pendek harus digunakan atau dijual terlebih dahulu sebelum barang dengan jangka waktu kadaluarsa yang lebih panjang [14]. [15] mengatakan bahwa Sistem inventaris yang paling baik dalam mengelola penyimpanan, pasokan, dan penanganan produk dengan masa simpan terbatas adalah FEFO. Keberadaan metode FEFO diklaim dapat meminimalkan kerugian dari bisnis yang sedang berlangsung.…”
Section: Pendahuluanunclassified
“…Metode FEFO atau First Expired First Out adalah metode manajemen persediaan yang didasarkan pada prinsip bahwa barang dengan jangka waktu kadaluarsa pendek harus digunakan atau dijual terlebih dahulu sebelum barang dengan jangka waktu kadaluarsa yang lebih panjang [14]. [15] mengatakan bahwa Sistem inventaris yang paling baik dalam mengelola penyimpanan, pasokan, dan penanganan produk dengan masa simpan terbatas adalah FEFO. Keberadaan metode FEFO diklaim dapat meminimalkan kerugian dari bisnis yang sedang berlangsung.…”
Section: Pendahuluanunclassified
“…Metode FEFO atau First Expired First Out adalah metode manajemen persediaan yang didasarkan pada prinsip bahwa barang dengan jangka waktu kadaluarsa pendek harus digunakan atau dijual terlebih dahulu sebelum barang dengan jangka waktu kadaluarsa yang lebih panjang [17]. [18] mengatakan bahwa Sistem inventaris yang paling baik dalam mengelola penyimpanan, pasokan, dan penanganan produk dengan masa simpan terbatas adalah FEFO. Keberadaan metode FEFO diklaim dapat meminimalkan kerugian dari bisnis yang sedang berlangsung.…”
Section: Metodeunclassified
“…Authors such as Linh et al [15] have demonstrated that this technique has brought several benefits such as the elimination of non-value-generating processes, increased process effectiveness, and improved worker performance since simplifying operations reduces the time spent on unnecessary activities like searching for inputs. In a case study developed in Peru, the use of the 5S tool in the company´s warehouses reduced product delivery delays by 28% [16]. Siva et al [17] showed that tools like 5S can help eliminate process inefficiencies in a service company.…”
Section: Smentioning
confidence: 99%